Influence of Environmental Technologies on the Economic Component in the Normalization of Thermal Conditions in Oil-Stores - ALABYEV, Vadim R.; KRUK, Marina N.; KOROBITCYNA, Mariia A.; STEPANOV, Igor S. (Journal of Environmental Management and Tourism, 2018)
Thermal conditions in petroleum tanks are important for maintaining optimal sanitary and hygienic standards, which contribute to increasing the working capacity of people. Therefore, the set problems are of great importance for research. The main goal of the work is to study the influence of environmental technologies on the economic component. To achieve this goal, the authors substantiated design solutions for the use of refrigeration equipment to improve and normalize thermal conditions in drilling galleries in the extraction of oil by underground. It is established that the main increase in air temperature is observed in the drilling gallery and on the outgoing air jet in the slope. According to the results of thermal surveys, it is determined that the cooling demand of the drilling gallery, provided that the air temperature at the end of the slope does not exceed 35.0°C, is about 1000 kW. It is established that the use of environmental technologies contributes to the improvement of working conditions. And also has a high level of profitability and payback.